Effect of soil organic matter on petroleum hydrocarbon degradation in diesel/fuel oil-contaminated soil - Chen, Yun-An; Grace Liu, Pao-Wen; Whang, Liang-Ming; Wu, Yi-Ju; Cheng, Sheng-Shung (Journal of bioscience and bioengineering, 2020)
The purpose of this study is to investigate the effect of soil organic matter (SOM) content levels on the biodegradation of total petroleum hydrocarbons (TPH). Batch experiments were conducted with soils with 2% or 10% organic matter that had been contaminated by diesel or fuel oil. In addition to the TPH (diesel or fuel oil) degradation efficiency, a comprehensive investigation was conducted on the TPH-degrading microbial community using molecular tools including oligonucleotide microarray technique and terminal restriction fragment length polymorphism analysis (T-RFLP). TPH was reduced from 10,000 mg/kg to 1849–4352 mg/kg dry weight soil. Higher biodegradation efficiencies and kinetic rate constants were observed in higher SOM contents. Hydrocarbon fractional analyses were conducted to explain the optimal operation with relatively low resin and aromatic fractions detected at the end of the remediation. The bacterial and fungal counts in the 10% SOM were approximately 10 CFU/g to 102 CFU/g above those in the 2% SOM, and the lowest fungal level was found when the least TPH degradability was measured. The internal transcribed spacer microarray identified the microorganisms that were introduced and proved their survival. The associated growth pattern confirmed that different kinds of contamination oils affected the microbial community diversity over time. Both the microarray and T-RFLP profiles indicated that Gordonia alkanivorans, G. desulfuricans, and Rhodococcus erythoropolis were the dominant bacteria, while Fusarium oxysporum and Aspergillus versicolor were the dominant fungi. The T-RFLP-derived nonmetric multidimensional scaling concluded that the dynamics of the microbial communities were impacted by the TPH degradation stages.